2011
DOI: 10.1590/s1808-86942011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of autologous fascia graft implantation into the rabbit voice muscle

Abstract: The ideal approach for the treatment of glottal insufficiency remains a challenge for laryngologists.Aim: This experimental study assessed the histological changes and fibrosis caused by autologous fascia lata grafts into the rabbit voice muscle.Study Design: A clinical and experimental study.Methods: A 0.2 × 0.2 cm fragment of autologous fascia lata was grafted into the right voice muscle of 14 adult rabbits. Animals were euthanized 30 or 60 days post-procedure and histology of the excised vocal folds was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…A previous study found that the FL could fuse well with muscle in a rabbit model. 24 To minimize the healing failure rates between the graft and remnant tendon, we designed a new STR technique using a FL autograft for irreparable posterosuperior MRCT or a severely degenerated tendon and muscle. As usual, the lateral ending of the FL was fixed on the footprint using the double-row technique.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that the FL could fuse well with muscle in a rabbit model. 24 To minimize the healing failure rates between the graft and remnant tendon, we designed a new STR technique using a FL autograft for irreparable posterosuperior MRCT or a severely degenerated tendon and muscle. As usual, the lateral ending of the FL was fixed on the footprint using the double-row technique.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the inflammation was graded by counting the number of predominant inflammatory cells infiltrated into the grafting areas and then graded as follows: Grade 0: no inflammatory cells, Grade I: 1–10 inflammatory cells, Grade II: 11–20 inflammatory cells, and Grade III: over 20 inflammatory cells. 12…”
Section: Experimental Designmentioning
confidence: 99%
“…Color intensity and arrangement of the collagen in 12 areas of surrounding tissue adjacent to the graft-bed were examined and graded after Masson’s Trichrome staining for the intensity of scarring. 12 Grade 0: No collagen fibers, Grade I: small amount of collagen with coarse arrangement and pale blue stain, Grade II: short to medium continuous arrangement of collagen bands around the graft with blue stain, Grade III: long collagen fibers around the graft with dark blue stain.…”
Section: Experimental Designmentioning
confidence: 99%
“…Pinna ve ark. yaptıkları hayvan çalışmasında fasya latanın stabil kaldığını, ödem, nekroz, yabancı cisim reaksiyonu ve önemli bir inflamasyona yol açmadığını göstermiştir [25]. Reijonen ve ark.…”
Section: Otolog Fasyaunclassified